Between philosophy and theology: contemporary interpretations of Christianity - Boeve, Lieven; Brabant, Christophe (Ashgate, 2010)
Richard Kearney's messianism : between the narrative theology of hermeneutics and the negative theology of deconstructionism / Lieven Boeve -- Introduction to the thinking of John Caputo : religion without religion is the way out of religion / Stefan Stofanik -- The sense of God : a theology of the event with special reference to Christianity / John Caputo -- Jean-Luc Nancy's deconstruction of Christianity / Joeri Schrijvers -- Introduction to the thinking of Graham Ward / Maarten Wisse -- De Certeau and an enquiry into believing / Graham Ward -- Introduction to the thinking William Desmond / Joris Geldhof -- On God and the between / William Desmond -- Religious experience and the phenomenality of God / Kevin Hart -- René Girard's contribution to political theology : competition and enmity / Wolfgang Palaver -- Introduction to Ellen Armour's thinking : race, sex and religion in postmodernity / Kristien Justaert -- Visual theology : diagnosing postmodernity / Ellen Armour -- Christianity and politics : a biographical-theoretical reading of Gianni Vattimo and Alain Badiou / Frederiek Depoortere -- Conclusion : lessons from philosophy for theology, and vice versa / Christophe Brabant & Lieven Boeve